1997
DOI: 10.1021/ef960165m
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sulfides and Thiols in Petroleum Distillates Using Solid-Phase Extraction and Derivatization with Pentafluorobenzoyl Chloride

Abstract: An improved method for differentiating sulfides, thiophenes, and thiols in petroleum distillates is presented. Thiophenes are separated from sulfides and thiols via solid-phase extraction. Reaction with pentafluorobenzoyl chloride is employed to form thiol esters, while sulfides do not react. Thiol elution times increase sufficiently after derivatization to provide separation from sulfides during gas chromatographic analysis. In addition, electron impact mass spectra of derivatized thiols exhibit an intense, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…These compounds have not previously been studied in produced water; however, their presence in oil has been shown (Beens and Tijssen, 1997;Thomson et al, 1997) and their toxicity towards bacteria or higher marine organisms investigated (Londry and Suflita, 1998;Falk-Petersen et al, 1985;Cajaraville et al, 1989). These two classes of compounds can undergo pentafluorobenzoyl derivatisation (Thomson et al, 1997) and may therefore be analysed by the same procedure as the one used for alkylphenols.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have not previously been studied in produced water; however, their presence in oil has been shown (Beens and Tijssen, 1997;Thomson et al, 1997) and their toxicity towards bacteria or higher marine organisms investigated (Londry and Suflita, 1998;Falk-Petersen et al, 1985;Cajaraville et al, 1989). These two classes of compounds can undergo pentafluorobenzoyl derivatisation (Thomson et al, 1997) and may therefore be analysed by the same procedure as the one used for alkylphenols.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of 1-Nph obtained were 10 to 50 times lower than the concentrations of alkylphenols with quite similar molar mass. Studies reported in the literature have pointed out difficulties in the identification of aromatic compounds with low molar mass in produced water; this is attributed to the tiny quantity of these compounds in produced water, as well as their similarity in terms of size and polarity, making this matrix a complex sample for the detection of this kind of compounds [46][47][48]. Thus, the proposed method shows that one can determine 1-Nph concentration in OPW sample with high reliability, good recovery rate, excellent selectivity, and under previously optimized conditions.…”
Section: Quantification Of 1-nph In Real Samplementioning
confidence: 99%
“…The thiols reported in fossil fuels had less than 10 carbon atoms. 19 On the contrary, Figure 4 indicated the presence of long alkyl chain thiols which have higher carbon numbers. The upper limits of carbon number for JH crude oil and the CHGO were more than 20 and 30, respectively.…”
Section: Michael Addition Reaction Of Model Thiols With Pvsmentioning
confidence: 99%
“…19 However, coelution of thiol derivatives (disulfides or thiol esters) with other sulfur species in GC was severe. 14,19 Recently, comprehensive two-dimensional gas chromatography (GC × GC) was used for identification of sulfur compounds by sulfur chemiluminescence detector (SCD) 20−23 and/or time-of-flight mass spectrometry (TOF MS); 22−25 however, very few thiols were detected due to the occurrence of abundant thiophenic and sulfidic sulfur compounds. 25 Thiols (e.g., cysteine and glutathione) were found in natural waters and play many important roles in aquatic ecosystems.…”
mentioning
confidence: 99%